Preparation of low-density polyethylene–silver ion antimicrobial film with and without ethylene-vinyl acetate. Issue 8 (October 2020) - Sahai, RSN; Gaval, VR; Bhat, B
The incorporation of antimicrobial agents into packaging materials is an effective method to inhibit the microbial population and aimed at specific microorganisms to provide better and safe products. The present study aims at developing an effective antimicrobial film with silver ions as an antimicrobial agent with and without ethylene-vinyl acetate (EVA). In the present work, two different masterbatches (MBs) were prepared. In the first case MB of 90%, linear low-density polyethylene (LLDPE) and 10% silver ions as an antimicrobial agent were prepared. In the second case MB of 80%, LLDPE, 10% silver ion, and 10% EVA were prepared. An antimicrobial film with low-density polyethylene and different percentages of the MB (0–30%) was prepared and tested under Japanese Industrial Standard (JIS Z 2801:2000) for Escherichia coli bacteria and Staphylococcus aureus bacteria. With the increase in the percentage loading of MB, the living amount of bacteria decreases. The decrease in the living amount of bacteria was greater when EVA was incorporated.